1999
DOI: 10.1017/s0022215100145438
|View full text |Cite
|
Sign up to set email alerts
|

Is Ollier's disease an understaging of Maffucci's syndrome?

Abstract: Ollier's disease and Maffucci's syndrome are similar multiple enchondromatous conditions. Other co-existing pathologies, particularly other primary malignancies, have been described sporadically in both conditions but more so in Maffucci's syndrome. Maffucci's syndrome is distinguished from Ollier's disease by the presence of haemangiomas in the former. In this report, a patient believed to have Ollier's disease for 44 years was subsequently found to have large splenic haemangiomas on magnetic resonance imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…It is well known that Maffucci , s syndrome is associated with an increased risk of malignancy 3 . In Maffucci , s original paper he noticed that these patients developed malignant neoplasms particularly in association with their enchondromatosis 18 .…”
Section: Maffuccimentioning
confidence: 99%
See 4 more Smart Citations
“…It is well known that Maffucci , s syndrome is associated with an increased risk of malignancy 3 . In Maffucci , s original paper he noticed that these patients developed malignant neoplasms particularly in association with their enchondromatosis 18 .…”
Section: Maffuccimentioning
confidence: 99%
“…Mellon et al 14 In several case reports, we found that at time of the diagnosis of chondrosarcoma, the patient was first considered to present Ollier's disease, but the concomitant diagnosis of a hemangioma indicated a correct diagnosis of Maffucci's syndrome [3][4][5][6]14,[26][27][28] .…”
Section: Maffuccimentioning
confidence: 99%
See 3 more Smart Citations